Study of lipid profile levels in malnourished and healthy children: a case control study acquired pneumonia in children - Dr. Ganesh Kumar Verma; Dr. Yogendra Singh Yadav; Dr. Rajesh Kumar Yadav; Dr. Indra Kumar Sharma; Dr. Kunwar Bharat; Dr. Krishan Kumar Yadav (Pediatric Review: International Journal of Pediatric Research, 2018)
Background: Under nutrition causes reduced growth and endocrine adaptations in order to maintain basic life processes. Protein energy malnutrition often coexists with micronutrient deficiencies. Malnutrition results from multiple deficiencies, not necessarily limited to lack of proteins or calories, but also involving other associated or separate factors such as deficiency of trace elements, such as copper and zinc and lipid profile. Methods: A case control study was carried out in department of Pediatrics, Maharani Laxmi Bai (MLB) Medical College, Jhansi from September 2009 to August 2010. 108 cases & 108 matched controls were recruited according to sex, weight and height after written informed consent with the approval of ethical committee. Total cholesterol and fractions (low-density lipoprotein cholesterol, high density lipoprotein cholesterol) and triglycerides concentrations were determined by automated enzymatic methods. The results were analyzed by the appropriate statistical test. Results: In present study, more than half children were suffered from marasmus as an acute malnutrition and most of children were of below 24 months of age. Total cholesterol, triglyceride and HDL levels were lower in PEM children while LDL & VLDL levels were higher in malnourished children group. Conclusion: The prevalence of under nutrition and dyslipidaemia observed in these children is a matter of concern considering the age group evaluated. These Biochemical parameters were found to be sensitive indicators for nutritional status and can be used for diagnosis of sub clinical case of protein energy malnutrition (PEM).